Manifestation of infantile scurvy in a skeleton from the high medieval village of Trutmanice (South Moravia, Czech Republic) - Račanská, Michaela; Vargová, Lenka; Dzetkuličová, Veronika; Vymazalová, Kateřina (Anthropologischer anzeiger, 2023)
The study describes the pathological findings recorded on the human remains of a 3 to 4-year-old child found in the burial site of Trutmanice (Czech Republic), dated to the 13th-15th century. The human remains were examined using standard macroscopic osteological and paleopathological methods, supplemented by radiographic examination. Although the preservation of the bones limited the analysis, multiple pathological changes were observed mainly on the skull: cribra orbitalia, small pores and fine deposits of newly formed bone tissue, hypertrophic diploë, grooves indicating rich branching of meningeal arteries on the intracranial surface of the cranial vault. A very fine periostotic deposition of newly formed bone tissue was also observed at the distal end of the diaphysis of the right tibia and both distal ends of the femora. The radiographs of the femora showed white lines of Frankel, scurvy lines, and Wimberger's rings. The observed pathological changes were possibly consistent with scurvy based on differential diagnosis. Reports about cases of juvenile scurvy from rural areas within the context of landlocked countries of Central Europe are rare. While scurvy is now more frequently reported in the paleopathological literature, evidence for scurvy within one of the most natural agricultural areas in the Czech lands remains rare. We recommend using radiographic examination to complement the diagnosis of scurvy in future paleopathological and epidemiological studies of past populations.
Keywords: kurděje; pohřeb; Humans; Child, Preschool; Scurvy; předškolní dítě; Body Remains; Czech Republic; Burial; Skull; Česká republika; tělesné pozůstatky; lidé; lebka